Sosialisasi Pencegahan Prilaku Bullying sebagai Implementasi Kurikulum Merdeka melalui Kegiatan Projek Penguatan Profil Pelajar Pancasila (P5) di SMAN 1 CiPeundeuy Kabupaten Subang - Nuraeni Nuraeni; Dhina Khoerunisa; Zikri Fachrul Nurhadi (Jurnal Media Pengabdian Komunikasi, 2025)
Bullying is a serious issue occurring in various parts of the world and can have negative impacts both physically and psychologically on all parties involved. Especially within the school environment, this issue must not be overlooked, as students at that age are undergoing a crucial stage of development that will influence their future. Efforts to prevent bullying can be carried out through various school activities, one of which is the implementation of the Pancasila Student Profile Strengthening Project (P5) program. This study aims to describe field findings related to the role of P5 activities in addressing bullying behavior.The approach method used in this student service activity was a community outreach on bullying prevention, combined with a participatory approach in which participants were expected to be actively involved throughout the activity. The counseling activity was held at SMAN 1 Cipeundeuy, Subang. The socialization process involved the delivery of core material by the speaker using a PowerPoint presentation. Overall, the activity succeeded in increasing participants’ knowledge about bullying among adolescents and it can be concluded that this socialization effort enhanced understanding of the risks and impacts of bullying on both physical and mental health. Keywords: Bullying Awareness, P5 Activities, Kurikulum Merdeka